Peptidergic Innervation of the Mammary Gland in the Pregnant, Lactating and Non-lactating Periods of Guinea Pig - Yaman, Mine; Tarakci, Berrin Gencer; Bayrakdar, Ali (Medwell Online, 2008)
The presence and distribution of some biologically active substances in nerve fibres supplying the mammary gland in the pregnant, lactating and non-lactating guinea pig were studied using immunohistochemical methods. The substances studied included: Calcitonon Gene Related Peptide (CGRP), substance P (SP), Vasoactive Intestinal Polypeptide (VIP), Galanin (GAL), Cholecystokinin (CCK) and neurotensin. Immunoreactive nerve fbres were associated with blood vessel, lactiferous ducts and alveoli. CGRP, SP, VIP, GAL, CCK and neurotensin immunoreactive fibres appeared to be much more numerous in the mammary gland of pregnant and lactating guinea pigs when compared to non-lactating guinea pigs. The results demonstrate a rich distribution of different types of nerve fibres in structures of mammary gland related to milk ejection. These nerve fibres may be involved in the local control of milk ejection.
Keywords: Nerve fibres; mammary gland; guinea pig; immunohistochemistry